CONFLICT OF REALITY AND FANTASTIC FICTION IN THE STORY OF ALEXEY N. TOLSTOY “COUNT CALIOSTRO” - Elena M. Kiryukhina (Russian Studies in Culture and Society)
The article examines the story “Count Cagliostro” by Alexei Nikolaevich Tolstoy, completed during the emigration period: based on a real historical fact (the visit to Russia in 1779-1780 of the Italian adventurer Giuseppe Balsamo, who called himself Count Cagliostro), it combines reality with fantastic fiction, and turning to works using a fantastic element is very relevant today. At first glance, the complex vicissitudes of life should have determined the preference of fantasy over reality, but in “Count Cagliostro” fantastic fiction enters into a conflicting relationship with the world of reality, proof of this thesis becomes the purpose of the article. Using problematic, comparative-contrastive, cultural-historical, chronological, and biographical methods, the author solves the goal by comparing “Count Cagliostro” with the story written at the same time – A.N. Tolstoy’s “Nikita’s Childhood” and the previously created poem by A.K. Tolstoy – “Portrait”, a simultaneous comparison of these works has not been previously made and represents the scientific novelty of the presented article. The author comes to the conclusion that in difficult times of moral searches A.N. Tolstoy does not want to hide from life’s problems in the world of a fantasy universe; the conflict between reality and fantastic fiction is resolved in favor of the triumph of real earthly love. This ability to prefer harsh reality to fairy-tale fiction will affect both the subsequent work and the life path of A.N. Tolstoy.